Cantáridas: uma trindade de sátiros na década de trinta - Fiuza, Felipe de Oliveira (2009)
In this thesis the following key elements are used as topic to start out an analysis of “Cantáridas e outros poemas fesceninos”, by Paulo Vellozo, Guilherme Santos Neves and Jayme Santos Neves: The fescenin, the satiric, the grotesque, the pornographic, carnavalization, and sodomy as well. The book began to be written in the 30s and actually it started up as a joke among the three partners, which essentially consisted in insulting each other through poems. Friends and relatives were also included in the process. The insult had to do with sexual orientation of the lash. By reviewing several poems of the book this essay seeks to sketch an overview as well as discuss the issues proposed as key elements within the theoretical carnavalization approach of Mikhail Bakhtin.